Predictors of upper tract damage in pediatric neurogenic bladder. Issue 5 (October 2017) - Prakash, Raghu; Puri, Archana; Anand, Rama; Jain, Ajay K.; Lal, Brahmanand; Garg, Vaibhav
Summary: Introduction: Upper tract damage (UTD) is a life-threatening complication of neurogenic bladder (NB). Early identification of risk factors for UTD and institution of remedial measures may probably prevent UTD. The aim was to study the predictors of UTD in children 2 years or older with NB. Method: This cross-sectional, observational study over 2 years included 30 children. UTD was defined as serum creatinine of >1 mg/dL or society of fetal urology grade III–IV hydronephrosis or hydroureteronephrosis on ultrasonography or renal scars on 99 m technetium dimercaptosuccinic scan or subnormal glomerular filtration rate (GFR) for age. The evaluated clinical variables were age at presentation, gender, palpable bladder lump, and recurrent urinary tract infection (UTI). Bladder wall thickness (BWT), grade and laterality of vesicoureteric reflux (VUR), status of the bladder neck, post-void residue (PVR), and level and type of intraspinal lesions were also noted. Urodynamic studies were performed for functional bladder assessment. A p -value <0.05 identified the risk factors. Results: UTD was detected in 15 (50%) with serum creatinine >1 mg% (2, 6%), SFU III–IV (11, 36%), renal scars (12, 40%), and subnormal GFR in (2, 6%) patients. Clinical risk factors for UTD were delayed presentation ( p = 0.034), palpable bladder lump ( p ≤ 0.001; OR 38.5; CI 5.6–262.5), and recurrent UTI ( p = 0.033, OR 4.125, CI 0.913–18.630). The presence of significant PVR, trabeculated bladder, spin-top urethra, and bilateral VUR were identified as radiological risk factors for UTD. Mean BWT in patients with and without UTD was 4.69 ± 1.78 mm and 2.91 ± 1.08 mm respectively. BWT predictive of UTD was 3.05 mm (Figure ). The mean detrusor leak point pressure (DLPP) did not vary significantly in those with and without UTD (36.82 ± 14.74 and 29.09 ± 10.44 cmH2 O, respectively), yet 75% patients with DLPP > 40 cmH2 O had UTD ( p = 0.038, OR 5.4, CI 0.84–34.84). DLPP <40 cmH2 O was associated with UTD in 35% patients. Discussion: The incidence of UTD in this series is in accordance with that reported with expectant management (40%) and is much higher than the 17% stated with proactive management. A limitation of this study is the small number of patients and heterogeneous clinical diagnosis. Conclusion: Delayed presentation with palpable bladder lump, recurrent UTI, increased BWT, bilateral VUR, increased PVR, and DLPP > 40 cm H2 O were identified as potential risk factors for UTD. This study highlights the significance of BWT as a predictor of UTD in NB. Figure Ultrasonogram of a child with neurogenic bladder with increased bladder wall thickness (BWT) and SFU grade IV hydroureteronephrosis. Yellow cross denotes BWT.